Summer festivals - Rosen, Mike (Wayland Hove, 1990)
The book Summer Festivals by Mike Rosen, published in 1991 by Hodder Wayland. This 32-page book is part of the "Seasonal Festivals" series and explores various religious and secular celebrations that occur during the summer months. It covers international festivals such as Midsummer, Obon, and the Fourth of July, among others. The book is illustrated with color photographs and artwork throughout, providing readers with a visual understanding of these diverse cultural events.